Síntese de catalisadores básicos na presença de surfactantes hexadeciltrimetilamônio - Assis, Flávio Morais de (2023)
The synthesis of two basic catalysts — CTA-MCM-41 and ZIF-8 — were studied in the presence of the surfactant hexadecyltrimethylammonium bromide (CTAB), which forms micelles in aqueous dispersions. The catalysts were characterized by X-Ray Diffraction, Thermogravimetry, Electron Microscopy, N2¬ Physisorption, Dynamic Light Scattering, Nuclear Magnetic Resonance etc.; and were tested in Knoevenagel condensation and transesterification reactions. It was demonstrated that CTAB micelles are particularly sensitive to the presence of added anions and can be morphologically altered, making the synthesis of CTA MCM-41 difficult, decreasing the number of its catalytic sites and, consequently, decreasing its catalytic activity in transesterification reaction. The use of CTAB in the synthesis of ZIF-8, in turn, causes a decrease in particle size and leads to the formation of nanosized particles. Furthermore, together with the amino acid L Histidine, it favors the formation of crystalline defect and facilitates agglomeration. ZIF-8 proved to be a promising catalyst in alkaline reactions, being slightly more active than CTA-MCM-41.